Analisis Yuridis Tindak Pidana Illegal Logging di Kawasan Hutan Sumatera Barat: Tinjauan Pengaturan Hukum Pidana Berdasarkan Undang-Undang Nomor 18 Tahun 2013 Tentang Pencegahan dan Pemberantasan Perusakan Hutan - Rahmad Sriyadi; Hasanuddin Hasim (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Illegal logging is a forest crime that causes severe damage to Indonesia’s forest ecosystems. Its impact is particularly evident in the forests of West Sumatra. This research aims to examine the criminal law provisions applicable to perpetrators of illegal logging. The study is based on Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction, which is also related to Law Number 41 of 1999 concerning Forestry.This research employs a normative juridical method. The approaches used include the statutory approach and the case approach. Legal data were collected through library research, encompassing legislation, court decisions, and relevant legal literature. The findings indicate that the criminal provisions governing illegal logging under Law Number 18 of 2013 are more comprehensive than those contained in previous regulations. The law provides for stricter criminal sanctions, regulates corporate liability, and establishes mechanisms for environmental restoration. However, the implementation of these provisions in the forests of West Sumatra continues to face various challenges, both in terms of regulatory substance and law enforcement.This study concludes that regulatory adjustments and the strengthening of law enforcement institutions are necessary to improve the effectiveness and sustainability of efforts to combat illegal logging